Molecular Genetic Medicine - Friedmann, Theodore, 1935- (Academic Press, 1992)
Molecular Genetic Medicine, Volume II, summarizes progress in several of the most important areas of modern molecular genetics and medicine. The chapters deal with ancient and common genetic diseases, a new infectious disease that threatens to become a world-wide scourge for all of humanity, and two of the most important and still poorly understood causes of mental retardation. The common thread winding through these separate stories is the astounding illumination of all these disorders by modern molecular genetic studies. The book opens with a chapter on the history of the molecular approach.